PENGARUH KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DIVIDEN, DAN KEPUTUSAN HUTANG TERHADAP NILAI PERUSAHAAN : (STUDI EMPIRIS PADA PERUSAHAAN SUBSEKTOR KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022) - M. Adam Majid Aditama; Retno Yuni Nur Susilowati (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of institutional ownership, dividend policy and decisions on the value of construction and building subsector companies listed on the Indonesian stock exchange for the 2018-2022 period. This research uses quantitative methods, data collection techniques with documentation methods, which involve collecting and evaluating secondary data from companies in the construction and building subsector which have been published by the Indonesian stock exchange for the 2018-2022 period. Data were analyzed using descriptive statistical methods and classification assumption tests. The results of the research show that institutional ownership has no effect on company value, dividend policy calculated using the dividend payout ratio method has a positive effect, and debt decisions calculated using the debt to equity ratio method have a positive effect on the value of construction and construction subsector companies listed on the Indonesian Stock Exchange period 2018-2022.